2021
DOI: 10.1038/s41598-021-97826-y
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate optimization of removing of cobalt(II) with an efficient aminated-GMA polypropylene adsorbent by induced-grafted polymerization under simultaneous gamma-ray irradiation

Abstract: Nowadays, radiation grafting polymer adsorbents have been widely developed due to their advantages, such as low operating cost, high efficiency. In this research, glycidyl methacrylate monomers were grafted on polypropylene polymer fibers by simultaneous irradiation of gamma-ray with a dose of 20 kGy. The grafted polymer was then modified using different amino groups and tested for adsorption of cobalt ions in an aqueous solution. Finally, the modified polymer adsorbent with a high efficiency for cobalt ions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…According to the findings, it is shown that monomers are swiftly bound on the surface of the polymer adsorbent when utilizing the simultaneous irradiation approach. This very effective adsorbent may be readily extracted from the solution and suggested as a potential use in the industry 73 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the findings, it is shown that monomers are swiftly bound on the surface of the polymer adsorbent when utilizing the simultaneous irradiation approach. This very effective adsorbent may be readily extracted from the solution and suggested as a potential use in the industry 73 .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of IDA-EDC MNWF, the peaks of epoxy and ester groups were reduced compared to GMA MNWF, and it was confirmed that new peaks of N-H were generated at peaks of 1554-1564 [48,54] and 1659-1662 cm −1 [46,51,54]. In addition, new peaks of the hydroxyl group (-OH) and N-H were generated at 3250-3400 cm −1 [47][48][49][50][51][52][53]55], confirming the introduction of IDA-EDC. In the case of NANA MNWF, the peak indicating C=O and the carboxyl group (COOH) was observed at 1726 cm −1 [47][48][49][50][51][52][53], significantly increased, and the hydroxyl group of 3250-3400 cm −1 [47][48][49][50][51][52][53]55] was also increased when compared with the peak of IDA-EDC MNWF.…”
Section: Introduction Of Functional Group Ida-edc and Nana Into Gma Mnwfmentioning
confidence: 94%
“…In addition, new peaks of the hydroxyl group (-OH) and N-H were generated at 3250-3400 cm −1 [47][48][49][50][51][52][53]55], confirming the introduction of IDA-EDC. In the case of NANA MNWF, the peak indicating C=O and the carboxyl group (COOH) was observed at 1726 cm −1 [47][48][49][50][51][52][53], significantly increased, and the hydroxyl group of 3250-3400 cm −1 [47][48][49][50][51][52][53]55] was also increased when compared with the peak of IDA-EDC MNWF. The introduction of NANA was confirmed by increasing the peak size of the carboxyl group and the hydroxyl group.…”
Section: Introduction Of Functional Group Ida-edc and Nana Into Gma Mnwfmentioning
confidence: 97%
See 1 more Smart Citation
“…35 Thus, effective polymerisation and simultaneous controlled grafting of a polymer on to the surfaces play an important role in tuning the properties of the resulting adsorbents, such as hydrophobicity, adsorption rate and capacity. 36 Moreover, a distillation precipitation polymerisation (DPP) technique is a combination of precipitation and radical polymerisation, which has the advantage of simple operation, fast fabrication procedure, scalable production and controllable polymerisation. 37 In this work, a magnetotactic bacteria-inspired fast and efficient nanorod adsorbent (MCSR-ATU) was first fabricated by magnetically induced assembly, followed by DPP of ATU, which was applied to capture gold from the e-waste.…”
Section: Introductionmentioning
confidence: 99%